The teaching of dentistry in the 21st century: where are we heading to? - Tisi-Lanchares, José Pablo (Revista Facultad de Odontología Universidad de Antioquia, 2018)
The 21st century has brought swift changes in organizations, due in part to current exponential technological advances. The academic programs in health are not an exception and the teaching in these areas has also been adapting to such changes. However, dentistry is rooted in medicine, whose systematic format stems from Ancient Greece. Empathy is a key element not only for patient-physician relationships but also for treatment success, so our dental teaching must pay attention to this element, which is often neglected because of our current “high-performance culture”.